KdV-based computer modeling of ion-acoustic solitons in complex plasmas with hot positrons and Bi-thermal electrons - Mohammad Nasir; Adeeba Riaz; Niaz Wali; Hifsa Saleem; Shumaila Ashiq; Muhammad Farhat Ullah; Sarra Ayouni; Mohamed Kallel; M. Ijaz Khan (Case Studies in Thermal Engineering, 2025)
An ion-acoustic solitons in a multicomponent plasma that comprises of hot positrons, hot and cold electrons, and isothermal or adiabatic ions is studied. A Korteweg-de Vries (KdV) expression governing the dynamic of weakly nonlinear solitary waves is obtained by employing reductive perturbation technique. The outcomes designate that the amplitude and width of rarefactive solitons are strongly affected by the temperature ratio of cold to hot electrons, the density ratio of positrons to electrons, and the composition of ion species. Under adiabatic ion conditions, numerical results confirm that enhancing the soliton speed makes the soliton narrower and more energetic, while enhancing the temperature difference between cold and hot electrons results in solitons that are broader and have a smaller amplitude. Furthermore, the impacts of positron density concentration and ion-to-electron temperature ratios on soliton profiles are deliberated. With applications on astrophysical phenomena like space weather and real-world applications in laboratory plasmas, where multicomponent interactions are obvious, this work proposed new perspectives on how nonlinear waves act in complex plasma environments.